Design of Truck and Bus Sales Information System Web-Based at PT. XYZ - Syamsiah Syamsiah; Agus Darmawan (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
As the number of competitors increases, the space for displaying products becomes limited, alternative choices become limited, marketing still relies on strategic locations and partners, and promotion is less effective and reach is still limited to certain locations. The purpose of this research is to create a web-based truck and bus sales system that does not depend on location and can easily expand its market share. In the economic field, technology and information play an important role. For example, in the context of buying and selling media, trucks and buses can be bought and sold from various sellers. At the XYZ Car Showroom it is still done manually, namely by coming directly to the showroom to see the trucks and buses that are being used. Meanwhile, visiting the showroom will take an unspecified amount of time and it is not certain that the desired car is in the showroom. To make it easier for members, a web-based car sales application was created. In this web design, the FIFO (First In First Out) method is used to ensure the latest information is always available. Where the first members will get the car or bus they want. With this online car sales application, it is hoped that it will make it easier for members of the XYZ Car Showroom to buy trucks and buses online.